2015
DOI: 10.1186/s10194-015-0581-x
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenic acid modulates experimentally induced inflammation in the trigeminal ganglion

Abstract: BackgroundThe trigeminal ganglion (TG) plays a central role in cranial pain. Administration of complete Freund’s adjuvant (CFA) into the temporomandibular joint (TMJ) elicits activation of TG. Kynurenic acid (KYNA) is an endogenous excitatory amino acid receptor blocker, which may have an anti-inflammatory effect. We hypothesize that KYNA may reduce CFA-induced activation within the TG.MethodsA local inflammation was induced by administration of CFA into the TMJ in rats. KYNA and kynurenic acid amide 2 (KYNAA2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 64 publications
2
43
0
Order By: Relevance
“…NMDA receptors are critical for the induction of spinal LTP (Liu and Sandk€ uhler, 1995). In the present work, we demonstrated that blocking NMDA receptors with D-AP5 suppressed HFSinduced CGRP increases ( Figures 2G and 2H), which is consistent with previous studies (Csá ti et al, 2015;Wong et al, 2014). Because synaptic functional plasticity leads to structural plasticity, the effect of the NMDA receptor antagonist D-AP5 on CGRP terminals may result from inhibition of spinal LTP.…”
Section: Action Potential Discharge In Nociceptive Afferentssupporting
confidence: 91%
“…NMDA receptors are critical for the induction of spinal LTP (Liu and Sandk€ uhler, 1995). In the present work, we demonstrated that blocking NMDA receptors with D-AP5 suppressed HFSinduced CGRP increases ( Figures 2G and 2H), which is consistent with previous studies (Csá ti et al, 2015;Wong et al, 2014). Because synaptic functional plasticity leads to structural plasticity, the effect of the NMDA receptor antagonist D-AP5 on CGRP terminals may result from inhibition of spinal LTP.…”
Section: Action Potential Discharge In Nociceptive Afferentssupporting
confidence: 91%
“…Previous work has shown a positive effect in TG following CFA injection into the temporomandibular joint [31] while SZR 72 decreased c-fos activation in the TNC in nitroglycerin induced trigeminal activation [32]. We have reported that one dose of SZR 72 is able to reduce dura mater applied CFA induced activation in the TG [16].…”
Section: Discussionmentioning
confidence: 83%
“…In our previous study, we investigated the effect of CFA on the expression of mitogen-activated protein kinases (MAPK), which play essential roles in pain processing. Administration of CFA in the TMJ caused significant extracellular signal-regulated kinase 1/2 (ERK1/2) and p38 MAPK increase in the TRG [42]. Dural administration of CFA resulted elevated ERK1/2, interleukin-1β and CGRP expression in the TRG [11], as well as increased c-fos and glutamate immunoreactivity in the TNC and cervical neurons [43].…”
Section: Role Of Neuropeptides In Preclinical Migraine Modelsmentioning
confidence: 99%